Prevalência e caracterização da dor em mulheres brasileiras - Souza, Marina Almeida de (Universidade Federal de São Carlos, 2025)
Pain is the main symptom that leads a person to seek medical care. It can be classified according to its mechanism of action and duration. Women are more likely to feel pain, as they suffer more from sensitivity and have more chronic pain than men. This may occur due to physiological mechanisms, biological and sociocultural factors. Objective: To analyze the factors associated with the interference of pain in the lives of Brazilian women. Methods: Cross-sectional study, conducted online, through Google Forms in which Brazilian women, over 18 years of age from all regions of Brazil were invited to answer a structured questionnaire that included questions about sociodemographic characteristics, presence of pain, and gynecological history. Women completed the Numerical Pain Scale (NPS) to assess the intensity of the pain they felt. The Brief Pain Inventory (BPI) was used to assess pain intensity and interference, in addition to having a body diagram in which women indicated the places where they felt pain. Furthermore, these women were asked about which health professionals they sought care for their pain, how many times they sought this medical care and whether the women considered that the professionals understood their complaints. Data analysis: The data were analyzed using the statistical software SPSS, version 0.20.01. Multiple linear regression analysis was applied using the enter method, considering a 95% confidence interval. The results were presented as mean, standard deviation (SD) and frequencies (%). For all analyses, a significance level of p > 0.05 was adopted. The study correlations were assessed by Pearson's correlation test and chi-square test. Results: 964 Brazilian women participated in this study and reported a mean pain intensity of 4 on the END scale. The most prevalent sites of pain were the head region anteriorly (64.2%), followed by the neck posteriorly (34.3%), right knee anteriorly (22.4%), lumbosacral region (20.4%) and head posteriorly (15.1%). Through multiple linear regression, the adjusted R2 was 0.318. It was possible to infer that there was a strong correlation between the score given by the interference by the BDI and the average pain. In addition, it was found that monthly family income, number of pregnancies, frequency of stress and average pain are directly related to the interference of pain in the lives of Brazilian women. In binary logistic regression, the average pain is related to pain interference, presenting an odds ratio of 1.696, and the frequency of stress presented an odds ratio of 6.426 (p=0.001). Conclusion: Given the findings, it is verified that sociodemographic factors directly influence the interference of pain in women and that the average pain and the frequency of stress predict pain interference. Therefore, it is essential that the assessment and management of pain consider not only the intensity of the symptom, but also the social, economic and cultural context of the patient.
Prevalence and characterization of pain in Brazilian women
Keywords: Dor; Prevalência; Localização; Saúde da mulher; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL